The Effectiveness of Behavioral Counseling as Intervention of Abasement, Aggression, and Endurance of High School Students - Gading, I Ketut (Jurnal Kajian Bimbingan dan Konseling, 2020)
This study aims to determine: (1) the effectiveness of behavioral counseling with assertive training techniques to increase the nature of abasement, (2) the effectiveness of behavioral counseling with shaping techniques to reduce the nature of aggression, and (3) the effectiveness of behavioral counseling with self-management techniques to increase the nature of endurance. This study employed an experimental study with a pre-test post-test control group. Participants involved were 37 class XI students of the Lab. School Undiksha. To recruit the participants, a purposive sampling technique was used by which the participants were students with low abasement, high aggression, and low endurance. Data were collected using scales that measure the nature of the abasement, aggression, and endurance. To test the hypothesis, the data were analyzed using the t-test. The results showed that: (1) behavioral counseling with assertive training techniques was effective for increasing the nature of abasement, (2) behavioral counseling with shaping techniques was effective to reduce the nature of aggression, and (3) behavioral counseling with self-management techniques was effective for increasing the nature of endurance.